LOSS OF HEMISPERMATOPHORES AND SEXUAL-BEHAVIOR OF TITYUS-BAHIENSIS (PERTY, 1834) (SCORPIONES, BUTHIDAE) - Matthiesen, F. A. (Science From Israel-division of Laser Pages Publ Ltd, 1993)
Male scorpions (Tityus bahiensis) that have been deprived of their hemispermatophores and hemispermatophore sheaths retain their ability to court females despite their inability to mate successfully. Although hemispermatophores usually regenerate rapidly in nature, no such regeneration occurred after experimental amputation.